Water-soluble substances of wheat: a potential preventer of aflatoxin B1-induced liver damage in broilers. (13th August 2018) - Wang, Xing-he; Li, Wei; Wang, Xing-hui; Han, Mei-yu; Muhammad, Ishfaq; Zhang, Xiu-ying; Sun, Xiao-qi; Cui, Xiao-xu
ABSTRACT: Aflatoxin B1 (AFB1) is very harmful for broiler production and public health. The water-soluble castoff in gluten production, i.e., the water-soluble substances of wheat (WSW) that contains 14% pentosan has positive effect on animal nutrient absorption, immunity, and antioxidation. Our study aims to investigate the preventive effects of WSW against AFB1-induced broiler liver injury. One day-old Arbor Acres broilers were randomly separated to 4 groups and were, respectively, fed with control diet, diet with 5 mg/kg AFB1 standard, diet with 5 mg/kg AFB1 standard and 214 ml/kg WSW, and diet with 214 ml/kg WSW continuously for 28 d. The histopathological, ultra-structural, and serological changes were tested to evaluate liver damage. The hallmarks of hepatocellular autophagy, apoptosis, and inflammation were measured by Western Blot and real-time polymerase chain reaction. The content of AFB1 in chicken liver was detected with an ultra-high performance liquid chromatography linked with the fluorescence detection method. The results showed that (i) WSW restored AFB1-induced changes in serum biochemical parameters, and ameliorated histomorphological changes in hepatocytes, (ii) WSW reduced the content of AFB1 in chicken liver, (iii) WSW alleviated AFB1-induced autophagy inhibition by up-regulating hepatic LC3, beclin-1, and down-regulating hepatic mTOR and cytoplasmic P53 expressions, (iv) WSW alleviated AFB1-induced hepatocellular apoptosis via inhibiting pro-apoptotic gene expression (nuclear P53, Caspase3, Bax), and promoting anti-apoptotic gene expression (bcl-2), (v) WSW feeding ameliorated AFB1-induced liver inflammation via impeding TLR4/NF-κ B and IL-1/NF-κ B signaling pathways, down-regulating pro-inflammatory cytokines (IL-1β , IL-6, and IL-8), and markedly up-regulating anti-inflammatory genes (IL-10 and HO-1). Conclusively, WSW is a potential preventer of AFB1-induced broiler liver damage by reducing the AFB1 content in liver, accelerating hepatocellular autophagy and inhibiting hepatocytes apoptosis and liver inflammation.